2013
DOI: 10.1377/hlthaff.2013.0239
|View full text |Cite
|
Sign up to set email alerts
|

Exempting Schoolchildren From Immunizations: States With Few Barriers Had Highest Rates Of Nonmedical Exemptions

Abstract: Rates of nonmedical exemptions from school immunizations are increasing and have been associated with resurfacing clusters of vaccine-preventable diseases, such as measles. Historically, state-level school immunization policies successfully suppressed such diseases. We examined state immunization exemption regulations across the United States. We assessed procedures for exempting schoolchildren and whether exemption rates were associated with the complexity of the procedures. We also analyzed legal definitions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
55
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 15 publications
2
55
0
1
Order By: Relevance
“…Nonmedical vaccine exemptions have been on the rise in the United States (1,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The rates of nonmedical vaccine exemptions are not evenly distributed among communities, which indicates that obtaining nonmedical vaccine exemptions tends to be a socially and spatially clustered behavior (27,28,36).…”
Section: Nonmedical Vaccine Exemptionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonmedical vaccine exemptions have been on the rise in the United States (1,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). The rates of nonmedical vaccine exemptions are not evenly distributed among communities, which indicates that obtaining nonmedical vaccine exemptions tends to be a socially and spatially clustered behavior (27,28,36).…”
Section: Nonmedical Vaccine Exemptionsmentioning
confidence: 99%
“…Several studies have suggested reasons for the resurgence of pertussis in the United States, including waning immunity from the acellular pertussis vaccine that replaced whole cell vaccine (9)(10)(11)(12)(13)(14)(15)(16)(17)(18); medical advancements that have allowed more effective diagnosis and reporting of pertussis cases (19,20); asymptomatic transmission of B. pertussis from individuals vaccinated with the acellular pertussis vaccine (21,22); evolving variant strains of B. pertussis circulating that are less protected by the vaccine (23)(24)(25); and a decrease in vaccine coverage that has compromised herd/community immunity (1,(26)(27)(28)(29)(30)(31)(32)(33)(34)(35). It is clear that the rise in reported pertussis cases in the United States is a multifaceted problem not fully captured in national or state-level data.…”
mentioning
confidence: 99%
“…In most states, the process of obtaining a vaccine exemption requires considerably less effort than fulfilling vaccination requirements, and the ease with which a personal belief exemption is obtained is directly correlated with the rate at which parents seek an exemption (2,52). Making receipt of a personal belief exemption more difficult is one reasonable solution to rising rates of exemption (19,48).…”
Section: Increasing the Difficulty Of Obtaining A Personal Belief Exementioning
confidence: 99%
“…15 States that offer personal-belief exemptions have had steady increases in the number of exemptions over time. Religious exemptions have increased for states that do not offer personal-belief/ philosophical exemptions but have, through regulatory language, broadly defined religion for the purposes of obtaining vaccine exemption.…”
Section: Exemption Rates and Legal Requirementsmentioning
confidence: 99%